If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(-5x + -3) + 2x + -4 = -34 Reorder the terms: 1(-3 + -5x) + 2x + -4 = -34 (-3 * 1 + -5x * 1) + 2x + -4 = -34 (-3 + -5x) + 2x + -4 = -34 Reorder the terms: -3 + -4 + -5x + 2x = -34 Combine like terms: -3 + -4 = -7 -7 + -5x + 2x = -34 Combine like terms: -5x + 2x = -3x -7 + -3x = -34 Solving -7 + -3x = -34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3x = -34 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = -34 + 7 -3x = -34 + 7 Combine like terms: -34 + 7 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| 5x+2(7x-17)=61 | | 3(8-b)-39=17b-5(3+4b) | | -10w+10=12w-12 | | -3k+0.3+4.4k-2.1k+4= | | 165=2x+3(7x-14) | | 4x^2-29x-63=0 | | -[15p-1]+24+2[5+5p]=0 | | 3a+20+x=180 | | (73x-58y)-(68x+15y)= | | .07-0.007x=.7 | | 17+13z=17+1 | | (64x+75y)-(-32x+7y)= | | tn=5+(n-1)3 | | 1/4-x=1/2x+9/4 | | (56x+46y)-(2x-7y)= | | y=-x^2+4x+6 | | (54x+63y)-(-31x+4y)= | | 2p+k=4 | | 6x-11y=10 | | 130=2x+6(2x-4) | | (78x-67y)-(49x+33y)= | | 3m+6m+7m-9= | | P-2k=7 | | 3/5x-1/5x=-3 | | n-5/7=4 | | 7(4)+4y=56 | | 7x+4(0)=56 | | 2y-3x=50 | | 16x^2-72x=15 | | 7(0)+4y=56 | | 1-(8)/(x+1)^3=0 | | (4x+2)/5*9=-18 |